Pengaruh Retail Marketing Mix Terhadap Unplanning Purchase Dicisions Pada Bisnis Minimart Di Desa Ubud Kabupaten Gianyar - Ni Luh Ketut Ayu Sudha Sucandrawati; Ni Luh Parmi Widiasih (Universitas Mahendradatta Denpasar, 2019)
The development of modern retail market today makes unplanned purchases or unplaning purchase dicisionsincreasing in society. This study aims to examine the effect of retail marketing mix on unplanned purchase desicions at Minimart shop in Ubud Village of Gianyar Bali Regency using sample of 86 people through slovin method. The analysis technique used is multiple linear regression analysis.The results of the analysis prove that retail marketing mix consisting of location, merchandise, pricing, promotion, atmosphere of outlets and retail service have a positive and partially significant effect on unplaning purchase dicisionsat Minimart shop in Ubud Village of Gianyar Bali Regency. Retail marketing mix consisting of location, merchandise, pricing, promotion, atmosphere of outlet and retail service have positive and significant influence simultaneously to unplaning purchase dicisionsat Minimart shop in Ubud Village of Gianyar Bali Regency.Suggestions that can be recommended to the management of Minimart in Ubud Village Gianyar regency of Bali to pay attention to matters related to retail marketing mix such as location, merchandise, pricing, promotion, atmosphere of outlets and retail service better in attracting visitors to do unplaning purchase dicisionsat Minimart in Ubud Village, Gianyar Regency, Bali. Locations provided for easily accessible visitors and ample parking. Merchandise provided to be more diverse in accordance with the needs of consumers. The price set to see the market competition so that consumers are willing to shop at Minimart. Providing attractive advertising and promotions to influence consumer purchases. The atmosphere in the booth is expected Minimart in Ubud Village Gianyar regency of Bali can provide wider space for visitors. Implementation of the maximum service in the service, ease of payment so as to attract unplaning purchase dicisionsin Minimart in Ubud Village Gianyar regency Bali.